Aplikasi Sistem Informasi Bengkel Sepeda Motor - Wong, Hendry; Wijayanti, Linda; Tanubrata, Markus; Yapinus, Pin Panji (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Business world, there are quite a lot of problems other than profitable income. Often there are errors in recording data that are the source of information from the business world. Likewise in the business world of a motorcycle repair shop, there are often errors in recording data both from the service or repair process and the sale of motorcycle spare parts and accessories. In the motorcycle repair shop business, errors often occur in recording spare part and accessory inventory because of the many types of spare parts and accessories. In addition, there are also several errors in calculating the total amount that must be paid by customers because they still use manual calculations as well as in refunds. Seeing these problems, an information system is needed that can overcome this problem, so an information system will be built by utilizing information technology both in terms of hardware and software that carries ease of use / user friendly. This Motorcycle Repair Shop Information System Application will be implemented with MySQL as a database and Java Netbeans as software and using the SDLC method in designing the information system. MySQL database and Java Netbeans are software that can be implemented in several operating systems such as Microsoft Windows, MacOS and Linux so they are not limited to just one operating system. Conclusions that can be obtained from the result of tcreating a Motorcycle Information System Application has provided convenience to employees in entering data in the form of spare part data, customer data or transactions so that errors in calculating the total amount to be paid by customers can be overcome because with this Motorcycle Workshop Information System Application all calculations are done automatically so that employees no longer experience difficulties or make errors in calculating the total amount. This application provides convenience and reduces errors that are commonly made by employees